Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.2353/ajpath.2008.070910
|View full text |Cite
|
Sign up to set email alerts
|

Liver Repopulation and Carcinogenesis: Two Sides of the Same Coin?

Abstract: Liver repopulation by transplanted normal hepatocytes has been described in a number of experimental settings. Extensive repopulation can also occur from the selective proliferation of endogenous normal hepatocytes, both in experimental animals and in the human liver. This review highlights the intriguing association between clinical and experimental conditions related to liver repopulation and an increased risk for development of hepatocellular carcinoma. It is suggested that any microenvironment that is able… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 74 publications
(110 reference statements)
3
45
0
Order By: Relevance
“…4B). Furthermore, the mean size of the three largest GST 7-7-positive nodules found ing the growth behavior of altered/nodular hepatocytes, as referred to in the Introduction (18). in each animal of the two groups was reduced by a factor of about 5 in transplanted versus nontransplanted rats…”
Section: Incidence Of Nodules In the Liver Of Dena+rs-repopulation Wementioning
confidence: 99%
See 3 more Smart Citations
“…4B). Furthermore, the mean size of the three largest GST 7-7-positive nodules found ing the growth behavior of altered/nodular hepatocytes, as referred to in the Introduction (18). in each animal of the two groups was reduced by a factor of about 5 in transplanted versus nontransplanted rats…”
Section: Incidence Of Nodules In the Liver Of Dena+rs-repopulation Wementioning
confidence: 99%
“…We have repeatedly shown that preexposure to RS sets the stage for extensive repopulation of the host liver The incidence of preneoplastic lesions was evaluated using immunohistochemical detection of the marker by transplanted normal hepatocytes (18). However, no studies had been published so far on the effect of a com-DPP-IV and GST 7-7 revealed that no overlapping was present between the two markers (i.e., none of the bined treatment with DENA and RS on liver repopulation.…”
Section: Statistical Analysis Hepatocyte Isolation and Transplantationmentioning
confidence: 99%
See 2 more Smart Citations
“…Silencing of the transgene is believed to be associated with clonal repopulation of the liver by hepatocytes that have either lost the transgene or shut down its expression. Clonal hepatocyte repopulation is known in other models of chronic liver disease, including human liver disease, to be a risk factor for HCC (Marongiu et al 2008;Alison et al 2009). Although the L protein overexpression model does not appear directly relevant to chronic hepatitis B, the idea of clonal hepatocyte repopulation may apply.…”
Section: Animal Models and Hccmentioning
confidence: 99%